Testing uncovered interest rate parity using LIBOR - Muhammad Omer; Jakob de Haan; Bert Scholtens (Center for Economic Studies and ifo Institute (CESifo), 2012)
We test Uncovered Interest Parity (UIP) using LIBOR interest rates for a wide range of maturities. In contrast to other markets, LIBOR markets have minimal frictions which could lead to rejecting UIP. Using panel unit root test suggested by Palm, Smeekes, and Urbain (2010) and cointegration techniques by Westerlund (2007), we find that UIP holds for short-term maturities, when market-specific heterogeneity is controlled for. Furthermore, the estimation results show that the speed of adjustment to the long-run equilibrium is proportional to the maturity of the underlying instrument.
Keywords: G12; G15; F31; 330; UIP; LIBOR; panel cointegration; Zinsparität; Laufzeit; Panel; Kointegration; Schätzung; Welt